Trajectories of memory and glance: a reflection on visual culture - Basia Nikiforova (Creativity Studies, 2019)
New book “Trajectories of Memory and Glance: a Reflection on Visual Culture” is an important contribution to the field of memory studies, which opens up a discussion about memory and visuality as two significant trajectories within the present world that have caused a culture change. This book aims to show how visual plane of memory actually covers a wide field and why memory and visuality are two “signatures” of our epoch, transforming the collective mindset. The structure of Trajectories of Memory and Glance is not linear: it works through the personal and collective categories of memory, nostalgia, art, culture and media, focusing on different groups and societies. The book consists of nine chapters that include such issues as interplay between memory and image, longing and communication, nostalgia and global consumer culture, topography of culture and memory, place and non-place, memory of Holocaust, paradigms of visibility and visuality, and others.